The voyage of Lucy P. Simmons - Mariconda, Barbara (Mariconda, Barbara. Voyage of Lucy P. Simmons, 2012)
"After Lucy P. Simmons's parents drown, Lucy must find a way to keep her greedy aunt and uncle from taking her family's house. A mysterious woman who seems to come from the sea, as well as the house itself, come to Lucy's aid"--